Extracellular Matrix and Growth Factor Engineering for Controlled Angiogenesis in Regenerative Medicine - Martino, Mikaël M.; Brkic, Sime; Bovo, Emmanuela; Burger, Maximilian; Schaefer, Dirk J.; Wolff, Thomas; Gürke, Lorenz; Briquez, Priscilla S.; Larsson, Hans M.; Gianni-Barrera, Roberto; Hubbell, Jeffrey A.; Banfi, Andrea (Frontiers in Bioengineering and Biotechnology, 2015)
Blood vessel growth plays a key role in regenerative medicine, both to restore blood supply to ischemic tissues and to ensure rapid vascularization of clinical-size tissue-engineered grafts. For example, vascular endothelial growth factor (VEGF) is the master regulator of physiological blood vessel growth and is one of the main molecular targets of therapeutic angiogenesis approaches. However, angiogenesis is a complex process and there is a need to develop rational therapeutic strategies based on a firm understanding of basic vascular biology principles, as evidenced by the disappointing results of initial clinical trials of angiogenic factor delivery. In particular, the spatial localization of angiogenic signals in the extracellular matrix is crucial to ensure the proper assembly and maturation of new vascular structures. Here we discuss the therapeutic implications of matrix interactions of angiogenic factors, with a special emphasis on VEGF, as well as provide an overview of current approaches, based on protein and biomaterial engineering that mimic the regulatory functions of extracellular matrix to optimize the signaling microenvironment of vascular growth factors.